Brain-derived neurotrophic factor is required for axonal growth of selective groups of neurons in the arcuate nucleus - Guey-Ying Liao; Karine Bouyer; Anna Kamitakahara; Niaz Sahibzada; Chien-Hua Wang; Michael Rutlin; Richard B. Simerly; Baoji Xu (Elsevier, 2015)
Objective: Brain-derived neurotrophic factor (BDNF) is a potent regulator of neuronal development, and the Bdnf gene produces two populations of transcripts with either a short or long 3' untranslated region (3' UTR). Deficiencies in BDNF signaling have been shown to cause severe obesity in humans; however, it remains unknown how BDNF signaling impacts the organization of neuronal circuits that control energy balance. Methods: We examined the role of BDNF on survival, axonal projections, and synaptic inputs of neurons in the arcuate nucleus (ARH), a structure critical for the control of energy balance, using Bdnfklox/klox mice, which lack long 3' UTR Bdnf mRNA and develop severe hyperphagic obesity. Results: We found that a small fraction of neurons that express the receptor for BDNF, TrkB, also expressed proopiomelanocortin (POMC) or neuropeptide Y (NPY)/agouti-related protein (AgRP) in the ARH. Bdnfklox/klox mice had normal numbers of POMC, NPY, and TrkB neurons in the ARH; however, retrograde labeling revealed a drastic reduction in the number of ARH axons that project to the paraventricular hypothalamus (PVH) in these mice. In addition, fewer POMC and AgRP axons were found in the dorsomedial hypothalamic nucleus (DMH) and the lateral part of PVH, respectively, in Bdnfklox/klox mice. Using immunohistochemistry, we examined the impact of BDNF deficiency on inputs to ARH neurons. We found that excitatory inputs onto POMC and NPY neurons were increased and decreased, respectively, in Bdnfklox/klox mice, likely due to a compensatory response to marked hyperphagia displayed by the mutant mice. Conclusion: This study shows that the majority of TrkB neurons in the ARH are distinct from known neuronal populations and that BDNF plays a critical role in directing projections from these neurons to the DMH and PVH. We propose that hyperphagic obesity due to BDNF deficiency is in part attributable to impaired axonal growth of TrkB-expressing ARH neurons.